Comparison of one-patch and standard 12-lead electrocardiogram - Townsend, Zachary; Werner, Tim (JOURNAL OF CARDIAC ARRHYTHMIAS, 2024)
Pre-connected and positioned patch devices have attempted to simplify the electrocardiogram (ECG) testing process. However, these devices have not been extensively tested and compared with standard ECG systems. The purpose of this study was to compare a novel patch-based ECG device with a standard 12-lead ECG system in order to determine clinical equivalence. Study participants underwent two consecutive ECG tests in a randomized fashion. ECG measurements (heart rate, PR, RR, QRS, QT intervals) were compared between the standard 12-lead ECG and the one-patch ECG. Paired t-test analysis was used for the comparisons conducted using GraphPad Prism. A total of 30 participants underwent the ECG testing (80% female; mean age 35 ± 16 years). One participant presented with first degree AV Block. All other participants were in normal sinus rhythm/sinus arrhythmia. There were no statistically significant differences identified in heart rate, PR interval, RR interval, QRS interval, and QT interval (p > 0.05) between the one-patch ECG and standard 12-lead ECG. These findings suggest that one-patch devices may provide equivalent ECG measurements compared with conventional 12-lead systems. Given the advantages of a one-patch, pre-positioned ECG system, this technology shows promising potential for cardiovascular screening.